National support for professional development of engaged scholars in higher education - Venter, K.; Holtzhausen, S. (South African Journal of Higher Education, 2025)
Although most South African universities have institutionalised community engagement, research indicates that engaged scholars need national support for professional development. This article focuses on the findings of a qualitative action research study undertaken by 11 board members of the South African Higher Education Community Engagement Forum (SAHECEF). The study’s appreciative inquiry summit method was steered by the question: How can SAHECEF become a flourishing community of praxis for national support of engaged scholars’ professional development? Guided by a semi-structured interview protocol, collective data generation occurred through paired appreciative conversations, while data analysis occurred in small and large group dialogues. The appreciative inquiry resulted in SAHECEF discovering its value-based best practices and organisational character strengths, serving as a foundation for designing an action plan to deliver national support for engaged scholars who profess the praxis of engaged scholarship.